ANALISIS MANAJEMEN STRATEGI PADA PENGELOLAAN TAMAN BUMI (GEOPARK) DI DAERAH ISTIMEWA YOGYAKARTA - Barata Setiya Budi, Rastra; Setia, Muda; Widiastuti, Nur (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study aims to determine the standard of Geopark management as a National Geopark or UNESCO Global Geopark, identify the non-optimal management of Geoparks in the Special Region of Yogyakarta (DIY), and identify the strategy of the DIY Regional Government to optimize Geopark management in DIY. This study measures the strategic management process in Geopark management in DIY using three stages, namely formulation, implementation, and evaluation, as well as using user perception analysis of the formulation, comparative analysis between Geopark management in DIY and other Geopark management, and comparative analysis between Geopark management formulations in DIY. with other Geoparks, as well as analysis of the projected performance of the management model formulation of Geopark management strategies in DIY. The results of this study indicate that (1) the standard for managing Geoparks on a national scale is the National Geopark Candidate Self-Assessment Document, while the Global Geopark is Document A UNESCO Global Geopark. (2) the causes of the non-optimal management of Geoparks in DIY, namely the strategic formula has not provided components that support optimal implementation, and the lack of clarity of the Geosite management network is the main cause of the non-optimal management. (3) the strategic management process since 2015 until now is a form of accountability for regional potentials and facilities for the welfare of the people in DIY. The depth of strategy formulations that have been published or those that have just been formulated can become an instrument for managing a UNESCO Global Geopark.